Спиральная S-матрица и рост кристаллов - Суздаль, В. С. (НТУ "ХПИ", 2015)
Рассматривается механизм роста кристалла винтовой спиралью, исходя из предпосылки о наличии в кристаллическом зародыше неисчезающей дислокационной ступеньки. Предложена матричная модель однозаходной дислокационной спирали типа Архимедовой на грани роста кристалла, в виде спиральной S-матрицы. Введено понятие спирали q-рода и показана практическая значимость S-матрицы, для выращивания кристаллов больших размеров по спирали c большим q.

The spiraling mechanism of the crystal growth by the helical spiral, in the assumption by the presence in a crystalline nucleus the non vanishing dislocation the step, is reviewed. Matrix model of a single-pass dislocation spiral the type of Archimedean on the edge of the crystal growth, in the form of a spiral S-matrix is proposed. The concept of q-kind the spiral is introduced and the practical importance of the S-matrix for growing large crystals on the spiral with large q is shown. The practical significance of the S-matrix is defined by the fact that the surface phenomena at the macro and micro levels of crystal growth are of considerable interest from the point of view of the development of nanotechnologies and other branches of science.
Spiral S-matrix and growth of crystals
Keywords: грань; модель; слой